2020
DOI: 10.1016/j.jad.2020.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors for anxiety during the coronavirus disease 2019 (COVID-19) epidemic among the teachers in China

Abstract: Highlights The overall prevalence of anxiety was 13.67% during the Coronavirus Disease 2019 epidemic among the teachers in China. The prevalence was higher for women than men (13.89% vs. 12.93%). After adjusting for potential confounders, age, sex, education status, type of teachers, school location, information source, worried level, fear level, and behavior status were found to be associated with anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
211
2
15

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(249 citation statements)
references
References 23 publications
(22 reference statements)
21
211
2
15
Order By: Relevance
“…First, the assignment was not randomized; however, it should be noted that a comparison between the intervention and the control group did not reveal any difference between participant’s characteristics on baseline; and a sensitivity analysis of mixed models with outcomes measures at baseline (T1) as covariates was conducted to control for possible differences in variables between the groups. Second, most of the participants in the study were female (86.6%) which are reported to experience higher work-related anxiety, more fear of COVID-19, and depression than male teachers [ 1 , 4 , 5 , 6 ]. However, we did not find differences between male and female participants in study outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the assignment was not randomized; however, it should be noted that a comparison between the intervention and the control group did not reveal any difference between participant’s characteristics on baseline; and a sensitivity analysis of mixed models with outcomes measures at baseline (T1) as covariates was conducted to control for possible differences in variables between the groups. Second, most of the participants in the study were female (86.6%) which are reported to experience higher work-related anxiety, more fear of COVID-19, and depression than male teachers [ 1 , 4 , 5 , 6 ]. However, we did not find differences between male and female participants in study outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…When Israel implemented social distancing restrictions, teachers had to rapidly adapt to a new format of distance learning. The pandemic has exposed teachers to many new challenges, such as increasing workloads, the need to learn and utilize new technologies, changes to daily teaching routines, fear of COVID-19, and uncertainty around how long distance learning will last, all while coping with full-time work from home [ 1 , 2 , 3 , 4 , 5 ]. Furthermore, the changes at work were accompanied by physical distancing from friends, colleagues, and students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 However, the prevalence rate varied from 6% to 50%. [22][23][24] Although there are scant data on how COVID-19 is increasing mental health conditions in Africa, some articles reported an increased rate of anxiety during the pandemic. [25][26][27] These discrepancies could be attributed to differences in assessment tools, study period (data was being anxiousness toward pandemic increase at beginning, then decrease and finally collected after a few months when the community gives less attention.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Arab study has indicated that this crisis has caused teachers to suffer problems that are often related to a pandemic situation, such as anxiety, depression, domestic violence, and divorce, all of which restrict their ability to teach properly ( Al Lily et al, 2020 ). A study carried out in three cities in China during the pandemic assessed the prevalence of anxiety among teachers and found a prevalence of 13.67%, with women being more anxious than men and the older ones being more symptomatic ( Li et al, 2020 ). Another study conducted in March also in China showed that the prevalence of stress symptoms in teachers was 9.1% and that it was important to support them psychologically ( Zhou and Yao, 2020 ).…”
Section: Introductionmentioning
confidence: 99%